Case Report: A Confirmed COVID-19 Patient with Type 2 Diabetes Mellitus - Sitepu, Annisa Nidya; Santi Syafril (TALENTA Publisher, Universitas Sumatera Utara, 2020)
COVID-19 is caused by a novel coronavirus known as SARS-CoV-2, a single chain RNA virus with a particle size of 120-160 nm. Covid-19 can affect almost all age groups, despite, the elderly and people who have records of chronic disease (co-morbid) have the risk to be affected more often and with worse complications from this disease. Diabetes mellitus (DM) is one of the risk factors for enhancing the severity of COVID-19 infection. A 26 years old man, was referred to the hospital with symptoms of shortness of breath, fever, and cough. The patient has no history of comorbidities, but his father has newly type-2 diabetes mellitus (T2DM). The patient was examined, with ad random blood sugar of 220 mg/dL and a chest radiograph suggesting bronchopneumonia. The patient was then examined for fasting and postprandial glucose, HbA1c, and diagnosed with DM, the patient's throat swab showed a positive COVID-19 result. Patients were then treated with antiviral, antibiotic, regulated insulin, and his blood sugar was monitored. The patient's blood sugar is stable and the patient discharge after 34 days of hospitalization.